Endocrine-Disrupting Chemicals and Early Puberty in Girls - Anastasios Papadimitriou; Dimitrios T Papadimitriou (MDPI AG, 2021)
In recent decades, pubertal onset in girls has been considered to occur at an earlier age than previously. Exposure to endocrine-disrupting chemicals (EDCs) has been associated with alterations in pubertal timing, with several reports suggesting that EDCs may have a role in the secular trend in pubertal maturation, at least in girls. However, relevant studies give inconsistent results. On the other hand, the majority of girls with idiopathic precocious or early puberty present the growth pattern of constitutional advancement of growth (CAG), i.e., growth acceleration soon after birth. Herein, we show that the growth pattern of CAG is unrelated to exposure to endocrine-disrupting chemicals and is the major determinant of precocious or early puberty. Presented data suggest that EDCs, at most, have a minor effect on the timing of pubertal onset in girls.